Poly(DL-lactic acid) scaffolds as a bone targeting platform for the co-delivery of antimicrobial agents against S. aureus-C.albicans mixed biofilms - Zegre, Miguel (2022)
FCT_UIDB/05608/2020. FCT_UIDP/05608/2020.